Sex-Specific Effect of High-Fat Diet on Glycerol Metabolism in Murine Adipose Tissue and Liver - Iena, Francesco Maria; Jul, Johanne Blanner; Vegger, Jens Bay; Lodberg, Andreas; Thomsen, Jesper Skovhus; Brüel, Annemarie; Lebeck, Janne (Frontiers in Endocrinology, 2020)
Obesity is associated with increased plasma glycerol levels. The coordinated regulation of glycerol channels in adipose tissue (AQP7) and the liver (AQP9) has been suggested as an important contributor to the pathophysiology of type-2-diabetes mellitus, as it would provide glycerol for hepatic synthesis of glucose and triglycerides. The regulation of AQP7 and AQP9 is influenced by sex. This study investigates the effect of a high-fat diet (HFD) on glycerol metabolism in mice and the influence of sex or GLP-1-agonist treatment. Female and male C57BL/6JRj mice were fed either a control diet or an HFD for 12 or 24 weeks. Liraglutide was administered (1 mg/kg/day) to a subset of female mice. After 12 weeks of HFD, females had gained less weight than males. In adipose tissue, only females demonstrated an increased expression of AQP7, which was paralleled by no increase in glycerol kinase expression or adipocyte size. 24 weeks of HFD resulted in a more comparable effect on weight gain and adipose tissue in females and males. HFD resulted in marked hepatic steatosis only in males and had no significant effect on the hepatic expression of AQP9. Liraglutide treatment generally attenuated the effects of HFD on glycerol metabolism. In conclusion, no coordinated upregulation of glycerol channels in adipose tissue and the liver was observed in response to HFD. The effect of HFD on glycerol metabolism is sex-specific in mice, and we propose that the increased AQP7 expression in female adipose tissue could contribute to their less severe response to HFD.